Bridging the development gap : ASEAN equitable development monitor 2014 - Beath, Andrew (2020)
Since the Asian Financial Crisis in the late 1990s and through the Global Financial Crisis of the last decade, commendable progress has been made by the member states of the Association of South East Asian Nations (ASEAN) in improving economic and human development outcomes both within each country and across countries. Since 1997, the economies of the poorest countries in the ASEAN, Cambodia, Lao PDR, Myanmar and Vietnam, have generally grown faster than the richer economies, which has reduced gaps in per capita incomes. Overall, child mortality rates have been cut by two-thirds across the ASEAN. And significant reductions have occurred even in some of the poorer member countries such as Cambodia and Lao PDR. However, this report The ASEAN Equitable Development Monitor (henceforth referred to as The Monitor), also shows that much remains to be done to ensure that the poorest members of the ASEAN community, within countries and across countries, are not left behind as the countries of the ASEAN integrate further. In both policies and development outcomes, differences across the countries of the ASEAN remain large. In this context, the monitor is designed to facilitate further discussion on policies and programs that can promote inclusive growth within ASEAN member countries and across the ASEAN community. It presents a number of indicators that are intended to provide a summary of development outcomes across and within the ten ASEAN countries and over time. On this basis, the monitor is intended to help policymakers in ASEAN member states to identify areas of concerns and prioritize national and regional interventions. The monitor tracks indicators across two broad sets of development outcomes and policies: (i) economic development; and (ii) human development.